2022
DOI: 10.3758/s13423-022-02225-7
|View full text |Cite
|
Sign up to set email alerts
|

Why do people overestimate the effectiveness of blocked learning?

Abstract: Interleaved learning has been shown to be better for delayed memory performance than blocked learning. Nevertheless, people judge blocked learning to be more effective. In the present work, we tested different explanations for this metacognitive bias. Across three experiments, participants studied sequences of object-color associations for a final color-reproduction test. In Experiment 1, colors of a sequence were selected from one color category (blocked-study condition) or distinct color categories (interlea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Finally, one recent study from our lab (Krasnoff & Overkott, 2022) also provided evidence for the role of working memory strength for JOLs. It is often observed that people prefer blocked than interleaved learning, and that they provide higher JOLs to the former than the later even though long-term learning is better for the interleaved learning condition.…”
Section: Jol Theories: Should Direct Access Be Reconsidered?mentioning
confidence: 82%
See 1 more Smart Citation
“…Finally, one recent study from our lab (Krasnoff & Overkott, 2022) also provided evidence for the role of working memory strength for JOLs. It is often observed that people prefer blocked than interleaved learning, and that they provide higher JOLs to the former than the later even though long-term learning is better for the interleaved learning condition.…”
Section: Jol Theories: Should Direct Access Be Reconsidered?mentioning
confidence: 82%
“…One major advantage of the revised memory-strength theory is that it is parsimonious and makes strong predictions that are easy to test. Finding that JOLs are not related to memory strength in a situation in which memory strength varies would provide conclusive evidence against the memory-strength theory (see also Krasnoff & Overkott, 2022). In contrast, the cue-utilization theory is hard to falsify.…”
Section: Discussionmentioning
confidence: 98%
“…Distributing study time over multiple sessions (i.e., distributed practice), for example, is a well-established learning strategy that is effective for many different types of material and is particularly fruitful for long-term retention [9][10][11] , but students -and especially younger ones-often fail to apply it 3 . Instead, they often improvise their study method and evaluate strategies based on how much they learned shortterm 12,13 . Our goal, therefore, is to investigate effective methods to help lower secondary school students integrate distributed practice into their self-study.…”
mentioning
confidence: 99%